Evaluación de la obtención de biogás mediante la digestión anaerobia de los residuos de fruta generados por una empresa de alimentos a escala laboratorio (2020)
The present work aims to generate an alternative for the use of citrus fruit peels (lemon, tangerine and orange) from a food company. The generation of a type of renewable and alternative energy such as biogas was evaluated, which is produced from the degradation of organic matter as a product of bacterial metabolism, through the anaerobic digestion process. For this, the anaerobic digestion in two stages with different organic loads was experimentally evaluated, varying the composition of the substrate and the addition of other compounds such as animal excrement (bovine manure), mineral substances and the addition of an inoculum from a methanogenic reactor.